(untitled) (Indian Journal of Public Health Research & Development, 2020)
Schizophrenia is a disease that affects various areas of individual function, including thinking, communicating, accepting, interpreting reality, feeling, and showing emotions. Non-pharmacological therapy given to overcome hallucinations of schizophrenic patients is cognitive therapy. The purpose of this study was to determine the effect of cognitive therapy on changes in hallucinatory symptoms in schizophrenic patients at Prof. Dr. M. Ildrem Mental Hospital in Medan. The design of this study is Quasi-Experimental One Group Pre and Post-test design, The study population was all hallucinatory patients with a total of 286 and a sample of 19 respondents. The sampling technique uses purposive sampling. Data collection tools using a questionnaire that has been tested for validity. The statistical test used is the paired t test. The results of this study obtained the value of p = 0,000 (p <0.05). In conclusion, there is a significant effect on changes in hallucinatory symptoms in schizophrenic patients before and after cognitive therapy.